Return to the Far Side of Planet Moore!: Rambling Through Observations, Friendships and Antics of Sir Patrick Moore - Mobberley, Martin (Springer, 2016)
The result of an exhaustive study of Sir Patrick Moore’s observations of the Moon and planets for more than 60 years, this book is a fantastic companion to the extremely popular, “It Came From Outer Space Wearing an RAF Blazer!” written by the same author. Moore recorded his telescopic observations in his logbooks, which are reproduced and described here in detail, along with his sketches and notes. In this light, the author discusses the factors that caused Moore to switch from lunar observing to planetary and variable star observing. He has also included personal recollections and humorous anecdotes from Moore’s friends and acquaintances, as well as a look at his best loved books. Further chapters describe Moore’s foreign travels and correspondence with those back home. Lastly, the author has not neglected a few of Moore’s most memorable television and radio appearances, which are examined along with a close up of what it was like to visit Moore’s beloved home of Farthings in Selsey. Essentially, this is a book written by popular demand from the readers of the author’s original biography, who craved more of Moore!